2018
DOI: 10.2478/cjece-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Estimation of Tourism Climatic Index (TCI) Based on Temperature-Humidity Index (THI)-Jordan Region Using Sensed Datasets

Abstract: Jordan which is located in the heart of the world contains hundreds of historical and archaeological locations that have a supreme potential in enticing visitors. The impact of clime is important on many aspects of life such as the development of tourism and human health, tourists always wanted to choose the most convenient time and place that have appropriate weather circumstances. The goal of this study is to specify the preferable months (time) for tourism in Jordan regions. Neural network has been utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Climate plays a key role in the sustainability of the tourism sector of a country [1] [2]. Studies have shown that the climate change is considered one of the most affecting factors in decision making for the selection of tourist destinations during holidays and other leisure activities [3]. Among several metrics and indexes that have been developed to study the influence of climate change in the field of tourism is the Tourist Climate Index (TCI).…”
Section: Introductionmentioning
confidence: 99%
“…Climate plays a key role in the sustainability of the tourism sector of a country [1] [2]. Studies have shown that the climate change is considered one of the most affecting factors in decision making for the selection of tourist destinations during holidays and other leisure activities [3]. Among several metrics and indexes that have been developed to study the influence of climate change in the field of tourism is the Tourist Climate Index (TCI).…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning (DL) [1] is protruded as a novel scope of machine learning, applied, and affecting several domains in our daily life such as medical image processing [2], prediction [3], mobile traffic classification [4], computer vision [5], computer networks [6]. DL's concept can be described as straightforward as the process of feature learning by machines as they ordinarily very well in the field of classification.…”
Section: Introductionmentioning
confidence: 99%